Relationship between markers of botanical origin in nectar and honey of the strawberry tree (Arbutus unedo) throughout flowering periods in different years and in different geographical areas. Issue 4 (4th May 2022) - Deiana, Vitale; Tuberoso, Carlo; Satta, Alberto; Pinna, Claudia; Camarda, Ignazio; Spano, Nadia; Ciulu, Marco; Floris, Ignazio
Abstract : The amounts of four well-recognized markers of the floral origin of strawberry tree honey (i.e., 2, 5-dihydroxyphenylacetic acid, homogentisic acid; (±)-2-cis, 4-trans-abscisic acid, c, t-ABA; (±)-2-trans, 4-trans-abscisic acid, t, t-ABA, and 2-(1, 2-dihydroxypropyl)-4, 8, 8-trimethyl-1-oxaspiro[2.5]oct-4-en-6-one, unedone) were measured in the nectar of the strawberry tree throughout the flowering periods of two years and at various sampling sites. The concentration of these compounds was also measured in reference to strawberry tree honey samples from the same geographical origin in order to establish correlations and verify the possibility that one (or more) of them may act as marker(s) of the purity level, i.e., of the amount of nectar by strawberry tree flowers that has been transferred to the relevant honey. The data obtained show that despite the existence of a good correlation level between the markers, none of them at the moment can be proposed as a marker of purity of this honey, due to very complex interactions between contamination by foreign nectars in strawberry tree honey and spatial (geographical origin of the samples) and temporal (year and flowering period) parameters. Among these compounds, homogentisic acid appears to be the most reliable marker of botanical origin of strawberry tree honey due to its higher concentration with respect to those measured for isomers of abscisic acid and unedone.